Cerebral Metabolic Crisis in Pediatric Cerebral Malaria - O'Brien, Nicole F.; Chetcuti, Karen; Fonseca, Yudy; Vidal, Lorenna; Raghavan, Prashant; Postels, Douglas G.; Chimalizeni, Yamikani; Ray, Stephen; Seydel, Karl B.; Taylor, Terrie E. (Journal of Pediatric Intensive Care, 2021)
Cerebral metabolic energy crisis (CMEC), often defined as a cerebrospinal fluid (CSF) lactate: pyruvate ratio (LPR) >40, occurs in various diseases and is associated with poor neurologic outcomes. Cerebral malaria (CM) causes significant mortality and neurodisability in children worldwide. Multiple factors that could lead to CMEC are plausible in these patients, but its frequency has not been explored. Fifty-three children with CM were enrolled and underwent analysis of CSF lactate and pyruvate levels. All 53 patients met criteria for a CMEC (median CSF LPR of 72.9 [interquartile range [IQR]: 58.5–93.3]). Half of children met criteria for an ischemic CMEC (median LPR of 85 [IQR: 73–184]) and half met criteria for a nonischemic CMEC (median LPR of 60 [IQR: 54–79]. Children also underwent transcranial doppler ultrasound investigation. Cerebral blood flow velocities were more likely to meet diagnostic criteria for low flow (<2 standard deviation from normal) or vasospasm in children with an ischemic CMEC (73%) than in children with a nonischemic CMEC (20%, p = 0.04). Children with an ischemic CMEC had poorer outcomes (pediatric cerebral performance category of 3–6) than those with a nonischemic CMEC (46 vs. 22%, p = 0.03). CMEC was ubiquitous in this patient population and the processes underlying the two subtypes (ischemic and nonischemic) may represent targets for future adjunctive therapies.
Keywords: cerebral malaria; cerebral blood flow; brain blood flow; brain disorders; metabolic; Doppler sonography; transcranial